Determination of Mercury in Fish (Otollithes ruber) and Canned Tuna Fish Marketed in Khuzestan and Shiraz, - A. Behzadnia , E. Rahimi (Journal of Chemical Health Risks, 2012)
In this study mercury was determined in canned tuna fish produced and distributed in Iran after digestion by the standard methods of AOAC. Mercury contents in fish and canned tuna fish were determined by cold vapor atomic absorption spectrophotometry. The metal contents expressed in mg/kg wet weight for mercury varied from 0.017 to 0.394 (average of 0. 089) and 0.023 to 0.529 (average of 0.146) in fish and canned tuna fish, respectively. The values were comparable and in the range of with the literature valves. The results of this study indicate that fish and tuna fish of produced and marketed in Iran have concentrations well below the standards FAO/WHO levels of these toxic metals and only one tuna samples exceeded the European dietary limit of 0.5 mg Hg/kg.